AB0760 SERIOUS INFECTIONS IN PATIENTS WITH RHEUMATOID ARTHRITIS AND PSORIATIC ARTHRITIS TREATED WITH TNFi: DATA FROM THE NOR-DMARD STUDY. (2nd June 2020) - Egeland Christensen, I.; Lillegraven, S.; Sexton, J.; Kvien, T. K.; Uhlig, T.; Aarrestad Provan, S.
Abstract : Background: Infection is an important complication in patients with rheumatoid arthritis (RA), especially when exposed to therapy with tumor-necrosis-factor-inhibitors (TNFi) compared to conventional syntethic DMARDs. The majority of studies have been in RA populations and less is known about the risk of serious infections (SIs) in patients with psoriatic arthritis (PsA). Objectives: To compare the incidence and risk of SI between RA and PsA patients treated with TNFi. Methods: The NOR-DMARD is a prospective observational multi-centre study. Patients diagnosed with clinical RA or PsA, starting treatment with a TNFi between Jan 2009 to Dec 2018 were included. SI was identified through linkage to the Norwegian Cause of Death Registry and the Norwegian Patient Register and defined as an infection requiring hospital admission with at least one-night hospital stay and/or as an infection causing death. A predefined list of ICD10 diagnosis for infections was used. Time at risk was defined as time from baseline to the first SI, 30 days after discontinuation of TNFi therapy, emigration or end of study period. Crude incidence rates (IRs) of SIs for RA and PsA were presented as events per 100 patient years at risk (PYR) and hazard ratios (HRs) were adjusted for age and gender. The risk of SI in PsA vs RA patients was estimated in cox-regression models adjusted for age and gender, and corrected for multiple observations. The models were stratified by age < 50 vs ≥ 50 years, gender, DAS28-CRP remission (<2.6) vs non-remission at 3 months, and use of methotrexate as co-medication. Results: A total of 3180 treatment courses on TNFi were identified (1780 RA and 1400 PsA) in 2368 patients (1356 RA and 1012 PsA) with 5697 person years at risk. The mean age in RA patients was 53.2 (SD 13.9), in PsA 48.2 (SD 11.9), p <0.001. 1542 (65 %) were women. Mean disease duration in years in RA patients was 10.0 (SD 9, 7) and 8.5 (SD 9.0) in PsA patients, with no significant difference in disease duration, p = < 0.001. There were 124 cases of SI in RA patients and 55 cases in PsA patients during treatment with a TNFi. The crude SI IRs were 4.00 (3.35, 4.76) in RA patients and 2.12 (1.63, 2.76) in PsA patients. Compared with RA patients, patients with PsA had a lower risk of SI (HR 0.64, 95 % CI 0.46-0.91) when adjusted for age and gender. The HR for females was (HR, p-value) (1.00, 0.97), age ≥ 50 was (1.80, 0.001), MTX co-medication (1.00, 0.99), DAS28-CRP >2.6 at 3 months was (1.20, <0.001) and for seropositives (0.95, 0.77). Conclusion: In patients starting treatment with a TNFi, the risk of SI was significantly lower in patients with PsA, compared to patients with RA, when adjusted for age and gender. The incidence rate of SI was lower in patients aged < 50, and in patients in DAS28-CRP remission for both PsA and RA patients. Disclosure of Interests: Ingrid Egeland Christensen: None declared, Siri Lillegraven: None declared, Joe Sexton: None declared, Tore K. Kvien Grant/research support from: Received grants from Abbvie, Hospira/Pfizer, MSD and Roche (not relevant for this abstract)., Consultant of: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Paid instructor for: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Speakers bureau: Have received personal fees from Abbvie, Biogen, BMS, Celltrion, Eli Lily, Hospira/Pfizer, MSD, Novartis, Orion Pharma, Roche, Sandoz, UCB, Sanofi and Mylan (not relevant for this abstract)., Till Uhlig Consultant of: Lilly, Pfizer, Speakers bureau: Grünenthal, Novartis, Sella Aarrestad Provan Consultant of: Novartis